Designing an efficient automated material flow - Makhkamov, Amir; Ek, David (My University, 2022)
Automation is a key technology that already has been implemented in the industry and is proven to be great aid to boost production capabilities. Most of the literature and previous research has demonstrated the benefits of automation when applied to manufacturing and production. However not as much research has been done using automation as a tool to enhance material handling within a company and material handling overall is less researched than manufacturing. This thesis uses literature, direct observation and data from a current material handling situation as base for the research. Automation is a key technology that can be applied in multiple cases. Different solutions can be used to maximize the positive benefits of implementing automation. Our findings indicate that implementation of automation by the use of AMR and Robot sorting within a material handling process can increase productivity and reduce manual labor needed within the process.
Keywords: Automation, Material Handling, AMR, RFID, Robot, Gripper, SCARCE